Revitalizing governance based on local wisdom in Papua - Silo, Akbar; Ismail, Ahmad (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2022)
The purpose of this study is to analyze whether local wisdom can be the foundation in mobilizing contextual governance to stimulate the presence of governance arrangements towards Good Governance in Papua. This research is a qualitative descriptive research, using a literature review approach. The data are from literature reviews, book journals, documents or data sources related to research. Data analysis includes the stages of data reduction, data presentation and data interpretation. Validate data through member checks or examine findings using written interpretations from academics in the field. The results of the study indicate that governance adopts elements of the cultural values ​​of the local community (tribes) which have been the reference for thinking and acting. Without it, the implementation of governance will not produce a significant overall impact. In the context of governance, the overall perspective of local values ​​is very helpful in adjusting the implementation of local government in Papua.